Penerapan Model Kesuksesan Delone dan Mclean pada Website Fakultas Ilmu Komputer (FILKOM) Universitas Brawijaya - Lely Hapsari Trihandayani; Ismiarta Aknuranda; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Information system success has a different understanding from technical view, semantic view, and effectiveness. To measure this success alone using only a few variables is not enough but must be measured in its entirety. DeLone emphasize this so that the measurement results can be more thorough than taking measurements only on certain variables. Variables used in this study are system quality, information quality, service quality, usage, user satisfaction, and net benefits. This study aims to do success analysis on FILKOM's website. FILKOM's website has a very important role as a media promotion for Faculty of Computer Science Brawijaya University and online services that provide information for students, lecturers, and other academic community. The implementation of DeLone and McLean models shows that the success rate on FILKOM website is moderate. The use of Pearson product moment analysis justifies the research hyphothesis that each variable has a positive and significant relationship on other variables connected according to DeLone and McLean models. Variables that have a strong influence on other variables are information quality and service quality on user satisfaction variables. Thus, to improve user satisfaction in using or accessing FILKOM website, SI departments must fix how the information provided to always fit with the needs of users and how users can contact the SI departments easily if there is an error.